Baseline Survey of the Knowledge of Physical Education and Sports Teachers in the Schools of Dar-Es-Salaam with respect to the Olympic Movement and their Attitudes towards teaching Physical Education - Tandau, Henry Benny (Πανεπιστήμιο Πελοποννήσου, 2011)
This study is a quantitative, descriptive research on the knowledge of Physical Education and Sports Teachers in the Schools of Dar-Es-Salaam with respect to the Olympic Movement and their attitudes towards teaching Physical Education. The study was carried out because the TOC together with TANOA intends to implement an Olympic Values Education Program (OVEP) through PE teachers, it is therefore important to understand the knowledge level of the PE teachers in relation to the Olympic Movement and their attitudes towards teaching Physical Education. A total of 43 PE teachers participated in the study; a questionnaire with four categories was used to collect the necessary data from PE teachers. Multiple choice questions on the Olympic Movement were asked to gauge the knowledge level, a 4-point Likert scale was used as the instrument to measure PE teachers attitudes to teaching physical education, while the PE teachers were also asked to state their background of teaching PE, their age, gender and whether they were trained to teach PE or not. They were also asked to give brief reasons as to their reactions to the Likert statements, in an attempt to find out more about their attitudes. The study illustrated a very low level of knowledge with respect to the Olympic Movement as most of the respondents 29 (67.44%) were below the passing mark of 50%. Only 14 (32.56%) managed to score above 50%. The overall mean score was 39.75% - way below the pass mark of 50%. On the other hand, results showed that in general, the respondents have a very favourable / positive attitude towards teaching PE, with an overall 40 (93%) favourable score. It is recommended that TOC / TANOA capitalize on the PE teachers’ positive attitude towards teaching physical education to spread knowledge of the Olympic Movement by organizing appropriate courses for the teachers on the Olympic Movement, It is also recommended that the TOC / TANOA do their best to convince Tanzania Institute of Education to include Olympic Knowledge in the PE Teachers Training Curriculum (currently under development).
Keywords: Physical education and training - Tanzania; Physical education for children - Tanzania; Physical education and training - Study and teaching -Tanzania; Φυσική αγωγή και εκπαίδευση - Τανζανία; Φυσική αγωγή για παιδιά - Τανζανία; Φυσική αγωγή και εκπαίδευση - Μελέτη και διδασκαλία - Τανζανία; Physical education; Olympic movement; Tanzania; Φυσική Αγωγή; Ολυμπιακό κίνημα; Τανζανία